Moderasi Beragama Dalam Pendidikan Persfektif Nahdlatul Ulama - Kaimudin; Ahmad Sofyan; Siti Munawaroh; Enday Mulyadi (Edusifa: Jurnal Pendidikan Islam, 2024)
Indonesia is a country with a population of various nationalities, languages, cultures and religions. The diversity of the Indonesian nation is enshrined in the motto Bhinek Tunggal Ika, which has different meanings, but is still one. When one does not understand, is not aware of, and does not want to understand the existence of diversity, there will be tension or radical action. it is in this context that the idea of religious moderation becomes important. One of the activities of NU in the field of education is learning and daily practice in real life. This practice should be aimed at students. This study is qualitative and fact-based and discusses religious moderation in education. The research method used is the study of literature. This study aims to determine the significance of religious moderation in NU's perspective education. Thus, this study attempts to explore and find things related to religious moderation in education. Diversity is the destiny of the Creator. Diversity will be a gift if we can manage it and use it properly, otherwise diversity will be a disaster if we cannot manage it. The main way to manage diversity is to know and understand each other. Religious moderation is very important to prevent extreme views leading to radical action, terrorism, and so on. Nahdalatul Ulama, as one of the largest organizations in Indonesia, is not silent about the emergence of these various ideologies and movements. To overcome the problem of radicalism, Nahdlatul Ulama put forward an idea, namely Islam Nusantara. The results of this study show that Nahdlatul Ulama is highly supportive of the idea of religious moderation or Islamic wasatiyah. Religious moderation is the key to creating tolerance and harmony. Islam calls upon its people to be tawazun (balance), tasamukh (tolerance), i'tal (straight and firm). These three characteristics are part of the religious moderation that must be instilled in students so that students will have moderate characteristics in the life of the nation and state. This study concludes that radicalism can be eradicated through education. Key words: religious moderation, education, Nahdlatul Ulama